2017
DOI: 10.1177/2048872616688419
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography is useful to predict postoperative atrial fibrillation in patients undergoing isolated coronary bypass surgery: A prospective study

Abstract: A history of atrial fibrillation and indexed left atrial maximal volume are the best predictors of the occurrence of postoperative atrial fibrillation following coronary artery bypass graft. The identification of high risk population of postoperative atrial fibrillation using these two factors could lead to the development of targeted strategies to limit this frequent complication in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Advanced age has been de ned as one of the most powerful risk factors for incident AF after open heart surgery [8,9]. This could be interpreted considering the presence of preexisting structural changes of the atria related to ageing and to arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced age has been de ned as one of the most powerful risk factors for incident AF after open heart surgery [8,9]. This could be interpreted considering the presence of preexisting structural changes of the atria related to ageing and to arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…the time between surgery and discharge, de ned as any sustained (i.e. >10 min) recorded episodes [6,8]. Antiarrhythmic agents, such as amiodarone, were most frequently used as a treatment option, alone or in combination with electric cardioversion.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Several prospective and retrospective studies have reported that a larger preoperative LA is associated with POAF after both cardiac valve surgery and CABG. [40][41][42][43][44][45][46][47] More advanced TTE measurements, such as speckletracking and strain analysis of the LA, have recently been investigated in numerous cardiac surgical populations. 44,[48][49][50][51][52] Impaired LA strain has a higher sensitivity in the prediction of POAF compared with measurements focusing solely on dilatation of the LA.…”
Section: Imagingmentioning
confidence: 99%
“…the time between surgery and discharge, defined as any sustained; i.e. > 10 min, recorded episodes [6,8]). The presence of pleural and pericardial effusion were evaluated postoperatively.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%